Comprehensive Midwifery Care for a Postpartum Mother with Postpartum Hemorrhage (PPH) due to Retained Placenta: A Case Report - Khomsiah, Nurul Fitri; Setyowati, Dewi; Andriyanti, Andriyanti (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Postpartum hemorrhage (PPH) remains the leading cause of maternal mortality. In Indonesia, the maternal mortality rate in 2023 was 189 per 100,000 live births, with hemorrhage as the dominant cause. Retained placenta is an important factor because it inhibits uterine contractions, especially in mothers aged ≥35 years, multiparous, anemic, and with chronic energy deficiency (CED). Case description: A 36-year-old multiparous woman (G4P3A0) with CED and mild anemia developed PPH after failure of placental delivery despite active management of the third stage. Estimated blood loss was ~1200 mL. Manual placental exploration, uterotonics, and fluid resuscitation were provided, followed by hospital referral. Ultrasound confirmed retained placental tissue, and curettage was performed. The patient stabilized after comprehensive treatment Discussion: Older maternal age, multiparity, chronic energy deficiency (CED), and anemia contribute to impaired myometrial contractility and failure of placental separation. Chronic energy deficiency (CED) and anemia reduce energy reserves and the oxygen-carrying capacity of uterine tissues, thereby increasing the risk of retained placenta and Postpartum hemorrhage (PPH). Conclusion: Retained placenta and Postpartum hemorrhage (PPH) are closely associated with maternal risk factors, including age ≥35 years, multiparity, anemia, and chronic energy deficiency (CED). Early detection of risk factors during antenatal care, as well as immediate and coordinated management in the third stage of labor, are very important to reduce maternal morbidity and mortality